Purification and characterization of laundry detergent compatible alkaline protease from Bacillus cereus - Banik R.M.; Prakash M. (My University, 2025)
An alkalophilic bacterium, Bacillus cereus produced an extracellular alkaline protease, which was found to be active at high temperature and pH range, suitable for commercial laundry detergents. B. cereus protease was partitioned in different aqueous two-phase systems such as PEG/dextran, PEG/potassium phosphate, PEG/sodium citrate, PEG/magnesium sulphate and PEG/sodium dihydrogen phosphate and best separation was found in PEG/potassium phosphate system. Therefore, production of protease was performed by the method of extractive fermentation in aqueous two-phase system composed of PEG 4000/potassium phosphate. Enhanced production was obtained in aqueous two-phase system as it overcomes the limitation of catabolic repression and product inhibition. The enzyme was purified to homogeneity by procedures including ammonium sulphate precipitation, concentration by ultrafiltration, anion exchange chromatography and gel filtration. The purified enzyme had specific activity 3256.05 U/mg and found to be a monomeric protein with a molecular weight of 28 kDa on sodium dodecyl sulfate/polyacrylamide gel electrophoresis (SDS-PAGE). Its maximum protease activity against casein was found to be at pH 10.5 and at 50°C. Proteolytic activity of the enzyme was detected by casein zymography, which gave a very clear protease activity zone on gel that correspond to the band obtained on SDS-PAGE with a molecular weight nearly 31 kDa. Protease was inhibited by specific serine protease inhibitors, suggesting the presence of serine residues at the active site of the enzyme.